2020
DOI: 10.1371/journal.pone.0234781
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of Functional Ice (FICE) on Salmonella-food safety, microbial spoilage and quality of raw poultry thigh meat during refrigerated storage

Abstract: In meat processing, antimicrobial treatment applied during slaughter and deboning may not control pathogens and spoilage organisms during subsequent transportation and storage. "Functional Ice" (FICE), an innovation over traditional ice, was investigated for its effects on food safety, shelf life, and quality of raw poultry thigh meat during refrigerated storage. FICE was prepared by freezing aqueous solutions of sodium tripolyphosphate (STPP) (2.5% and 5% w/v) and sodium lactate-sodium diacetate (SL-SD) (1% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…En este canal, es fundamental el seguimiento de las tendencias a utilizar a la hora del empaquetado y la cadena de frío [91], el empaquetado correcto permite aislar el producto de contaminantes externos [92], esta condición de aislamiento se debe mantener de forma rigurosa hasta el primer contacto con el consumidor [93]. La cadena de frío desde la planta hasta antes de consumir es primordial,al igual que en el transporte debido a que el producto por lo general tiene distribución por vía terrestre, marítima o en muchos lugares del mundo mediante tren, con trayectos muy largos antes de llegar a su lugar de distribución, conjuntamente con factores de clima y geográficos [94].…”
Section: Bacterias Presentes En El Transporteunclassified
“…En este canal, es fundamental el seguimiento de las tendencias a utilizar a la hora del empaquetado y la cadena de frío [91], el empaquetado correcto permite aislar el producto de contaminantes externos [92], esta condición de aislamiento se debe mantener de forma rigurosa hasta el primer contacto con el consumidor [93]. La cadena de frío desde la planta hasta antes de consumir es primordial,al igual que en el transporte debido a que el producto por lo general tiene distribución por vía terrestre, marítima o en muchos lugares del mundo mediante tren, con trayectos muy largos antes de llegar a su lugar de distribución, conjuntamente con factores de clima y geográficos [94].…”
Section: Bacterias Presentes En El Transporteunclassified
“…Głuchowski et al [58] concluded that the sous-vide method lowered cooking losses and extended the shelf life of analysed chicken breasts in comparison to conventional boiling and steaming. Other research investigates the effect of functional ice, which includes food-grade ingredient solutions within the water matrix and potentially contributes to an improvement of meat shelf life and quality, especially with poultry (e.g., Kataria et al [59]).…”
Section: Reduction Potential Practical Implementations and Further Re...mentioning
confidence: 99%